2015
DOI: 10.1111/chso.12115
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the ‘Child at Risk’ in Social Work Reports: A Way of Seeing is a Way of not Seeing

Abstract: In the context of the changing relationship between children, parents and the welfare state, professionals have to deal with notions of the "child at risk". In child welfare and protection, the issue of normative judgement in (risk) assessment and documentation is an essential area for exploration for social workers. We examine the practice of report writing in which future professionals exercise power while assessing, documenting, and judging the child as "at risk". We report on a study about a fictional soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…There is a dissonance between a legal and moral imperative and an ambiguous practice imperative which emphasizes technical competence in truth‐telling recordkeeping (Roets et al, 2015) at the point of social work qualification. Professional standards for social workers in England require the maintenance of ‘clear, accurate, legible and up to date records, documenting how I arrive at my decisions’ (Social Work England, 2021, 3.11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a dissonance between a legal and moral imperative and an ambiguous practice imperative which emphasizes technical competence in truth‐telling recordkeeping (Roets et al, 2015) at the point of social work qualification. Professional standards for social workers in England require the maintenance of ‘clear, accurate, legible and up to date records, documenting how I arrive at my decisions’ (Social Work England, 2021, 3.11).…”
Section: Discussionmentioning
confidence: 99%
“…As the findings of this study demonstrated, through the acts of creating and representing the assessment in a textual format, the social worker effectively frames the child or young person as a subject and effectively reframes their narrative. Roets et al (2015) differentiate between the case record as a medium for truth-telling, in which the content of a record represents a professionally constructed structured objective reality and the case record as a medium for a more unstructured and reflexive storytelling narrative, which acknowledges the complexities inherent in social work relationships. The ICS and other contemporary evolved electronic recording systems have been designed to record social work activities within an 'atomized' structure (Hall et al, 2010, p. 394).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes parents do not even know about their children having an IEP (Isaksson et al 2007). When a student is segregated and placed outside the parents' home, the placement represents a kind of embedded disqualification of both parents and student (Hall et al 2006;Roets et al 2015); it is interesting to investigate the enrollment of parents and students in this special situation.…”
Section: Increased Importance Of Documentationmentioning
confidence: 99%
“…This account of rhetoric is not limited to words alone, but also to the materiality of practice and the ways in which persuasive forms emerge from them (see, for example, Barnett & Boyle, 2016;Enoch, 2019). Hence, rhetoric's relevance to social work has been claimed by several writers for its significant re-emphasis on 'the classical relationship between theoria and praxis through a realization of theory's practical power' (Parton, 2000, p. 461;see also Miller, 1991;Roets et al, 2015;Rutten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%